Study on the Microscopic Pore Structures of Coal Measure Reservoirs in the Shanxi Formation, Eastern Ordos Basin - Pengfei, Jiao; Pengwan, Wang; Shangwen, Zhou; Huaichang, Wang; Xiangyang, Chen (Frontiers in Earth Science, 2022)
The Carboniferous-Permian coal measures in China contain abundant natural gas resources. Shale, coal and tight sandstone reservoirs are developed in coal measures, and the quantitative characterization of the pore structures of different types of reservoirs can provide scientific guidance for the sweet spot prediction of tight reservoirs. In this study, taking the Shan 2 Member coal measure of the Shanxi Formation in the eastern Ordos Basin as an example, the pore structures of shale, coal rock and tight sandstone were systematically studied based on organic geochemistry, scanning electron microscopy, high-pressure mercury injection, and low-temperature N2 and CO2 adsorption experiments. The results show that the microscopic pore structures of different types of reservoirs in the Shan 2 Member coal measures are quite different. Shale and tight sandstone mainly develop clay mineral pores at mesopore scale, followed by intragranular and dissolution pores developed in quartz and feldspar minerals, while organic pores are rarely developed. A large number of macro-scale clay mineral pores and micro-fractures are developed in tight sandstone, meanwhile the pore connectivity of tight sandstone is better than that of shale. A large number of micro to nano-scale organic pores are developed in coal, and the specific surface area of micropores in coal is much larger than that of mesopores in shale and tight sandstone. Sandstone, shale, and coal are frequently interbedded in coal measure strata. Tight sandstone provide the main storage space for free gas, and pores in shale and coal absorb a large amount of natural gas. Sandstone-shale-coal assemblages and sandstone-coal assemblages are the key targets for the exploration of hydrocarbons in the Shanxi Formation coal measures in the study area.